Tumbuhan Berkhasiat Obat Suku Dayak Seberuang Di Kawasan Hutan Desa Ensabang Kecamatan Sepauk Kabupaten Sintang - Irwan Lovadi, Damianus Muda Takoy, Riza Linda, (Jurnal Protobiont, 2013)
Medicinal plants are non-timber products frequently used by people around the forest. Dayak (local tribe) Seberuang compound in Sintang is in the forest area in Ensabang village in Sepauk sub-district. The increasing deforestation in West Borneo every year is threatening flora conservation which is potential to be medicinal plants; therefore, an effort to conserve it are needed. This paper aims to look at the kinds, the used and the process of making the plants used by Seberuang tribe in forest area in Ensabang village. This study took place from February 2013 to June 2013. The data was collected through survey and interviews people in three villages that are Sungai Jaung village, Sungai Tamang village and Tanah Kaya village. Respondents are selected using the method of snowball sampling starting from the chief of the tribe who then recommends other respondents. The result of the research shows that there are sixty (60) medicinal plants from thirty four (34) families. They are able to cure 31 (thirty one) diseases. The plants which are predominantly used are from Zingiberaceae family. Leaves of the plant are mostly used as the drugs. Medicinal plant habitat is mainly taken from the forest.